2017
DOI: 10.1080/14647273.2017.1335886
|View full text |Cite
|
Sign up to set email alerts
|

Embryo culture using a time-lapse monitoring system improves live birth rates compared with a conventional culture system: a prospective cohort study

Abstract: In this prospective cohort study, the effects of a time-lapse monitoring system on embryo quality and clinical pregnancy outcomes were assessed. A total of 608 patients undergoing in vitro fertilization between April 2013 and June 2014 at our institution were recruited for this study and group-matched into a time-lapse monitoring (TLM) (N = 304) or a standard incubator (SI) (N = 304). The patients' characteristics in the TLM and SI groups were not significantly different. The TLM group showed a significantly h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 33 publications
1
23
0
Order By: Relevance
“…Furthermore, since TLI can assess embryos without removing them, embryos are not exposed to changes in temperature, humidity, light, gas concentrations, and pH, which can impair embryonic development (Fujiwara et al 2007;Zhang et al 2010). However, few studies have compared the performances of TLI culture systems to standard incubators (SI) (Alhelou et al 2018; Barberet et al 2018;Sciorio et al 2018;Wu et al 2017). Our previous study showed that TLI had a higher transferable embryo ratio than the SI group on Day 3 (Wu et al 2017), which was consistent with other studies (Alhelou et al 2018;Barberet et al 2018;Sciorio et al 2018).…”
Section: Introductionsupporting
confidence: 86%
“…Furthermore, since TLI can assess embryos without removing them, embryos are not exposed to changes in temperature, humidity, light, gas concentrations, and pH, which can impair embryonic development (Fujiwara et al 2007;Zhang et al 2010). However, few studies have compared the performances of TLI culture systems to standard incubators (SI) (Alhelou et al 2018; Barberet et al 2018;Sciorio et al 2018;Wu et al 2017). Our previous study showed that TLI had a higher transferable embryo ratio than the SI group on Day 3 (Wu et al 2017), which was consistent with other studies (Alhelou et al 2018;Barberet et al 2018;Sciorio et al 2018).…”
Section: Introductionsupporting
confidence: 86%
“…It also runs morphological, dynamic and morphokinetic parameters. These factors can be used to estimate embryo viability and implantation potential (Coticchio et al, ; Kim et al, ; Wu et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Wu et al analyzed a total of 608 patients, which was divided into two equal groups (time-lapse and standard incubator culture system) with 304 patients in each group. They found that the ongoing pregnancy rate and the live birth rate in time-lapse group were higher than that of the standard incubator culture system 16 . Siristatidis showed in a study population (of 239 women) that the women were classified into two groups: time-lapse and conventional monitoring.…”
Section: Discussionmentioning
confidence: 94%
“…There was no statistically significant difference between two groups in clinical pregnancy and implantation rates 13 . Some studies only analyzed cleavage embryo selection in order to compare the effectiveness of morphokinetic versus morphologic criteria in embryo selection 9,16,43 . Wu et al analyzed a total of 608 patients, which was divided into two equal groups (time-lapse and standard incubator culture system) with 304 patients in each group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation